The role of polymorphism of genes of the I and II phase of xenobiotics biotransformation in the development of recurrent and chronic bronchitis in adolescent-smokers - Il'chenko S.I.; Fialkovskaia A.А.; Kramarenko N.N.; Makukh G.V. (Medičnì Perspektivi)
The purpose of research – to study the role of allelic polymorphism of genes of the I and II phases of xenobiotics biotransformation in the development of reccurent and chronic diseases of the respiratory system in adolescent-smokers. There was carried out molecular-genetic study of the polymorphic locus Т3801С of gene CYP1A1 and polymorphic locus A313G of gene GSTP1 in adolescent-smokers with recurrent and chronic bronchitis. It is established that TТ genotype of the polymorphic locus Т3801С of gene CYP1A is a marker of resistance to the development of this pathology in adolescent-smokers. The presence of CC genotype of the polymorphic locus Т3801С of gene CYP1A1 and GG genotype of polymorphic locus of A313G GSTP1 gene may be considered as a possible risk factor for the development of chronic inflammatory process in bronchopulmonary system. Thus, the introduction of molecular-genetic methods of research opens up new possibilities in diagnosis of recurrent and chronic diseases of the respiratory system. Based on the analysis of genetic factors in children and adolescents, it will be possible to predict the risk of COPD developing in the future; this will allow doctors to carry out the necessary preventive activities among risk groups.